2018
DOI: 10.1177/0972150918779167
|View full text |Cite
|
Sign up to set email alerts
|

Equity Values and Prediction of Earnings with Disaggregation of Earnings in India

Abstract: This article examined the relative performance of aggregated and disaggregated earnings for valuation of equity and prediction of earnings in India. We measured three levels of earnings disaggregation: aggregate earnings, total accruals and cash flows, and four major constituents of accruals, then we estimated pooled as well as individual industry-wise regressions. We adopted Barth, Beaver, Hand and Landsman’s (1999, Review of Accounting Studies, 4(3, 4), 205–229; 2005, Journal of Accounting, Auditing & Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous research has shown that predictive power is better when aggregate is decomposed into its constituent items (Hodgson & Russell, 2014;Banks et al, 2018); while Kubota et al, (2011) concluded that OCI components are more relevant in valuation and prediction than OCI in the aggregate. The study conducted by Kumari & Mishra (2018), Hafij Ullah Mohammad (2013) also concluded, that the prediction of future earnings will increase when earnings are decomposed into accrual earnings and operating cash flows compared to aggregate earnings. Meanwhile, Willett (2016) research results show that when CI is decomposed into NI and OCI, it is proven to be more able to increase the relevance value of OCI.…”
Section: Earnings Attribution To the Owner And Aggregate Comprehensive Incomementioning
confidence: 99%
“…Previous research has shown that predictive power is better when aggregate is decomposed into its constituent items (Hodgson & Russell, 2014;Banks et al, 2018); while Kubota et al, (2011) concluded that OCI components are more relevant in valuation and prediction than OCI in the aggregate. The study conducted by Kumari & Mishra (2018), Hafij Ullah Mohammad (2013) also concluded, that the prediction of future earnings will increase when earnings are decomposed into accrual earnings and operating cash flows compared to aggregate earnings. Meanwhile, Willett (2016) research results show that when CI is decomposed into NI and OCI, it is proven to be more able to increase the relevance value of OCI.…”
Section: Earnings Attribution To the Owner And Aggregate Comprehensive Incomementioning
confidence: 99%